Design of a hyperstable 60-subunit protein icosahedron - Hsia, Yang (2016)
The icosahedron and the dodecahedron are the largest of the Platonic solids, and icosahedral protein structures are widely utilized in biological systems for packaging and transport1,2. There has been considerable interest in repurposing such structures3–5, for example, virus-like particles for the targeted delivery and vaccine design. The ability to design proteins that self assemble into precisely specified, highly ordered icosahedral structures would open the door to a new generation of protein 'containers' that could exhibit properties custom-made for various applications. In this manuscript, we describe the computational design of an icosahedral nano-cage that self-assembles from trimeric building blocks. Electron microscopy images of the designed protein expressed in E. coli reveals a homogenous population of icosahedral particles nearly identical to the design model. The particles are stable in 6.7 M guanidine hydrochloride at up to 80 °C, and undergo extremely abrupt, but reversible, disassembly between 2 M and 2.25 M guanidinium thiocyanate. The icosahedron is robust to genetic fusions: one or two copies of superfolder GFP can be fused to each of the 60 subunits to create highly fluorescent standard candles for light microscopy, and a designed protein pentamer can be placed in the center of each of the twenty pentameric faces to potentially gate macromolecule access to the nanocage interior. Such robust designed nanocages should have considerable utility for targeted drug delivery6, vaccine design7, and synthetic biology8.